THE EFFECT OF AGILITY TRAINING ON DRIBBLING SKILLS USING THE INSIDE OF THE FOOT AT SSB BARONA U10–14 YEARS - Maulidansyah Maulidansyah; Zulheri Is; Munzir Munzir; Irwandi Irwandi; Salbani Salbani (Program Studi Pendidikan Jasmani, FKIP Universitas Bina Bangsa Getsempena, 2025)
The ability to dribble using the inside of the foot among players of SSB Barona U11-14 is still suboptimal, and there is a lack of variation in the training that could enhance sprinting performance. To address this issue, agility training could be implemented. This study aims to examine the effect of agility training on dribbling skills with the inside of the foot in SSB Barona U10-14 players. The research employs a quantitative approach with an experimental method and a one-group pretest-post-test design, involving 16 training sessions. The study population consists of all 32 players from SSB Barona U10-14. The sampling technique used is total sampling, meaning all 32 players were included in the study sample. Data collection was carried out using a dribbling test developed by Subagyo Irianto et al. (2010), which has a validity of 0.779 and reliability of 0.559. Data analysis involved calculating the mean, standard deviation, and performing a t-test for differences in mean scores. The results indicate that agility training significantly influences dribbling skills with the inside of the foot in SSB Barona U10-14. This is supported by the calculated t-value of 7.98, which exceeds the t-table value of 1.69 at a significance level of α = 0.05 (df = 30).